Effect of Irrigation on the Manuring of Sugarcane Crop-Part I Vegetative Growth Index (Area and Dry Weight of Leaves) - Prasad, Sheonath (Journal of Soil and Water Conservation, 2022)
Different workers have selected different parts of plants as Growth ' index in order to know the growth behaviour of plants under diverse conditions. and others in Maritius and clements in Hawaii have studied correlations of vegetative index and Vegetative relations of Primary ' index with the yield and sucrose of cane. These authors have shown that the index can be used as a guide to fertilization and management of sugarcane crop.The conception to discover one prime motivative or inducive force in plants which can successfully integrate all other factors for correlation with growth is gaining ground. This is because it becomes easier to advise the growers on account of the simplicity of the analytical procedure. The theory of which is said to be a Foliar diagnosis good substitute for soil analysis aims at finding the deficiency by utilizing the technique and interpretation of the leaf analysis. Going one step further it may be index or the realized that the 'Growth 'Primary' index are being investigated by the crop physiologists for obtaining facts in more simpler manner than what was so far at- tempted through soil and plant analysis. In the present study leaf area of sugarcane which, as a single factor, might correlate with the growth as a resultant effect of the external and internal growth-promoting factors has been measured. The measure- ment was done on the field in a manurial cum irrigational experiment laid out for the purpose. Besides this morphological study the total dry weight of the leaf samples and the soil moisture were also estimated to furnish additional information. The experi- mental details and the discussions on the results are given below.